Structural and Biochemical Characterization of the YaxAB Pore-forming Toxin from Yersinia Enterocolitica - Bräuning, Bastian; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2019)
This book discusses the decoding of the lytic mechanism of an α-helical pore-forming toxin, YaxAB, composed of two different subunits. Pore-forming toxins (PFTs) are among the most common bacterial toxins. They are produced by a variety of pathogens, which infect a wide range of organisms including plants, insects and humans. Yet the maturation of these particles and the structural changes required for pore formation are still poorly understood for many PFT families. Using a diverse panel of biochemical and structural techniques, including X-ray crystallography and cryo-electron microscopy, Dr. Bräuning and colleagues have succeeded in identifying the mechanistic contributions of the two toxin components and elucidating the lytic state of the pore complex. The results of this thesis on the YaxAB system are applicable to orthologues from agriculturally relevant insect pathogens, and offer valuable structural and mechanistic insights to inform future bioengineering efforts. .
Introduction -- Objectives -- Materials & Methods -- Results -- Discussion.
Keywords: Industrial microbiology; Proteins .; Analytical chemistry; Biotechnology; Bacteria; Industrial Microbiology; Protein Biochemistry; Analytical Chemistry; Chemical Bioengineering; Bacteria